A Study of Usage and Usability of Intelligent Personal Assistants in Denmark - Bogers, Toine; Al-Basri, Ammar Ali Abdelrahim; Ostermann Rytlig, Claes; Bak Møller, Mads Emil; Juhl Rasmussen, Mette; Bates Michelsen, Nikita Katrine; Gerling Jørgensen, Sara (Information in Contemporary Society, 2019)
Intelligent personal assistants (IPA), such as Siri, Google Assistant, Alexa, and Cortana, are rapidly becoming a popular way of interacting with our smart devices. As a result, there has been a wealth of research on all aspects of IPAs in recent years, such as studies of usage of and user satisfaction with IPAs. However, the overwhelming majority of these studies have focused on English as the interaction language. In this paper, we investigate the usage and perceived usability of IPAs in Denmark. We conduct a questionnaire with 357 Danish-speaking respondents that sheds light on how IPAs are used in Denmark. We find they are only used regularly by 19.9% of respondents and that most people do not find IPAs to be reliable. We also conduct a usability study of Siri and find that Siri suffers from several issues when used in Danish: poor voice recognition, unnatural dialogue responses, and an inability to support mixed-language speech recognition. Our findings shed light on both the current state of usage and adoption of IPAs in Denmark as well as the usability of its most popular IPA in a foreign-language setting.